DIVERSITY AND RELATIVE ABUNDANCE OF NATIVE ARBUSCULAR MYCORRHIZAL FUNGI ASSOCIATED WITH CUCUMBER PLANTS IN KANO STATE, NIGERIA - Yakasai, Umma Abdurrahman; Rabiu, Safianu (FUDMA JOURNAL OF SCIENCES, 2025)
Arbuscular mycorrhizal fungi (AMF) are ubiquitous soil microorganisms within the phylum Glomeromycota that form mutually beneficial associations with the roots of over 80% of terrestrial plants. In this study, soil samples were collected from the rhizosphere of cucumber plants at three farms in the Kura agroecological region of Kano State, Nigeria. AMF species were isolated and identified using the wet sieving and sucrose centrifugation method. A total of eight morphologically distinct AMF species, representing the genera Gigaspora, Septoglomus, Archaespora, Acaulospora, and Glomus, were recovered. Spore abundance varied significantly among the sites, with Site A yielding the highest density (53.00 ± 5.89 spores per 50 g of soil), followed by Site B (43.00 ± 5.99) and Site C (33.33 ± 2.89). The variation in AMF diversity and abundance suggests that both biotic and abiotic factors critically influence community structure. These findings provide baseline data that may inform the selection of indigenous AMF species for use as biofertilizers to enhance cucumber growth and soil fertility. Further molecular analyses are recommended to complement the morphological identification and to elucidate the functional roles of AMF in these agro-ecosystems.
Keywords: Arbuscular Mycorrhiza; Symbiosis; Photosynthates; Isolation; Identification